2015
DOI: 10.1007/s00216-015-8541-5
|View full text |Cite
|
Sign up to set email alerts
|

Automated solid-phase extraction coupled online with HPLC-FLD for the quantification of zearalenone in edible oil

Abstract: Established maximum levels for the mycotoxin zearalenone (ZEN) in edible oil require monitoring by reliable analytical methods. Therefore, an automated SPE-HPLC online system based on dynamic covalent hydrazine chemistry has been developed. The SPE step comprises a reversible hydrazone formation by ZEN and a hydrazine moiety covalently attached to a solid phase. Seven hydrazine materials with different properties regarding the resin backbone, pore size, particle size, specific surface area, and loading have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(23 citation statements)
references
References 18 publications
0
23
0
Order By: Relevance
“…Analytical standards of ZEN (100 μg mL -1 in acetonitrile), α-ZEL (solution in acetonitrile 10 μg mL -1 ) and β-ZEL (solution in acetonitrile 10 μg mL -1 ) were obtained from Sigma-Aldrich (Taufkirchen, Germany). Zearalenone-14-glucoside (ZEN14Glc) was synthesised and purified in our laboratory [ 4 ], as well as cis -zearalenone [ 14 ]. Zearalenone-16-glucoside (ZEN16Glc) was kindly provided by Prof. Franz Berthiller (IFA-Tulln, University of Natural Resources and Life Science, Vienna).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Analytical standards of ZEN (100 μg mL -1 in acetonitrile), α-ZEL (solution in acetonitrile 10 μg mL -1 ) and β-ZEL (solution in acetonitrile 10 μg mL -1 ) were obtained from Sigma-Aldrich (Taufkirchen, Germany). Zearalenone-14-glucoside (ZEN14Glc) was synthesised and purified in our laboratory [ 4 ], as well as cis -zearalenone [ 14 ]. Zearalenone-16-glucoside (ZEN16Glc) was kindly provided by Prof. Franz Berthiller (IFA-Tulln, University of Natural Resources and Life Science, Vienna).…”
Section: Methodsmentioning
confidence: 99%
“…Although ZEN largely occurs as trans -isomer, it has been reported that cis -ZEN may be formed upon light exposure and in water, in presence of some ionic species [ 13 ]. The cis -isomer is usually overlooked in food analysis, but its presence in edible plant matrices has been reported and in mammals its metabolites have comparable estrogenicity as trans -ZEN [ 14 16 ]. In infected cereals, ZEN may undergo conjugation through glycosylation; zearalenone-14-glucoside (ZEN14Glc) is its most known masked form [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Comparing with other sample preparation approaches previously reported for oil analysis, all recoveries of the present MSPE UPLC-MS/MS method are good. As shown in Table 4, analytical figures of this method are compared for several HPLC-based quantitative methods reported for analysis of mycotoxins in oils (Ferracane et al 2007;Majerus et al 2009;Drzymala et al 2015;Li et al 2015).…”
Section: Quantification Of Mycotoxins In Vegetable Oil Samplesmentioning
confidence: 99%
“…Other research groups use prepacked cartridges, well plates, or disks for automated solid‐phase extractions 6–9. With the preparation of immobilized materials, the combination of liquid and solid handling on an automated platform can be realized.…”
Section: Introductionmentioning
confidence: 99%